sRAGE in diabetic and non-diabetic critically ill patients: effects of intensive insulin therapy - Arabi, Yaseen M (BioMed Central, 2011)
INTRODUCTION: Hyperglycemia represents an independent prognostic factor in critically ill non-diabetic patients but not in those with diabetes. In this context, there is an ongoing debate on the benefit of an intensive insulin therapy, particularly in diabetic patients. We tested the hypothesis that expression of the receptor for advanced glycation end-products (RAGE), an important signal transduction receptor that elicits long-lasting nuclear factor kappa B (NF-κB) activation, may underlie this difference. RAGE expression is regulated by multiple ligands, including high mobility group box-1 (HMGB-1), and is reflected by its released soluble form (sRAGE). METHODS: A predesigned analysis was conducted of prospectively collected samples from 76 hyperglycemic critically ill patients (33 type-2 diabetes, 43 non-diabetes) aged ≥18 years with blood glucose of > 6.1 mmol/L enrolled in a randomized controlled trial comparing intensive insulin therapy with conventional insulin therapy. sRAGE and its ligand HMGB-1 together with IL-6, and soluble thrombomodulin (as markers of inflammation and endothelial cell injury, respectively) were evaluated in ICU, at Days 1, 3, 5 and 7. Plasma samples from 18 healthy subjects were used as controls. RESULTS: Both diabetic and non-diabetic hyperglycemic patients showed increased plasma sRAGE, HMGB-1 and soluble thrombomodulin levels at the time of admission to ICU. Plasma IL-6 concentration was only increased in non-diabetic patients. Plasma levels of sRAGE were higher in diabetic compared with non-diabetic patients. Intensive insulin therapy resulted in a significant decrease of sRAGE and thrombomodulin at Day 7, in diabetic but not in non-diabetic patients. Circulating sRAGE levels correlated positively with IL-6 and soluble thrombomodulin levels and inversely with HMGB-1. Multivariate regression analysis demonstrated that sRAGE remains independently correlated with HMGB-1 only in diabetic patients. Neither sRAGE nor any inflammatory markers are associated with mortality. CONCLUSIONS: These findings support the hypothesis that sRAGE release, time-course and response to intensive insulin therapy differ between hyperglycemic diabetic and non-diabetic critically ill patients. Whether this difference underlies the dissimilarity in clinical outcome of hyperglycemia in these two conditions warrants further studies.